Evaluation of the kinematic viscosity in biodiesel production with waste vegetable oil, ultrasonic irradiation and enzymatic catalysis: A comparative study in two-reactors. (1st September 2018) - Murillo, Gabriel; Sun, Jianzhong; Ali, Sameh S.; Yan, Yunjun; Bartocci, Pietro; He, Yaojia
Graphical abstract: Highlights: The optimal ultrasonic power was 15%, and the decoupling power of 50% at 20 kHz. The kinematic viscosity was reduced 80% in the first 2.5 min in the reactor tank. The least kinematic viscosity was obtained in the packed-bed reactor after 5 reuse cycles. Burkholderia cepacia lipase showed a stable activity after its use in both reactors. Abstract: In order to evaluate the biodiesel (BD) quality in a batch and a packed-bed reactor (PBR), a comparison was carried out in terms of the kinematic viscosity. Waste vegetable oil (WVO) and Burkholderia cepacia lipase were utilized as the main substrate and enzymatic catalyst, respectively. In the batch reactor, a kinematic viscosity of 36.75 mm 2 .s −1 at 20 °C was obtained in the first 2.5 min and 24.78 mm 2 .s −1 after 3 h with the application of ultrasound, without stirring. In the PBR, the lowest kinematic viscosity value was of 7.88 mm 2 .s −1 at 20 °C, and 5.83 mm 2 .s −1 at 40 °C, after 5 doses of 30 mL of methanol per round. The BD in both reactors was mainly produced by esterification of free fatty acids. The final mixture in the PBR met the requirement of kinematic viscosity of ASTM D6751-10, GB/T 19147-2003, and GB/T 265-1988 standards, respectively. Upon comparing the performance in both reactors, despite the limited BD yields, a common pattern of fast reduction in the kinematic viscosities was observed at the first reaction stages (approximately 70–80% reduction). Then flat-shape values were measured in the last reaction stages. At applying further strategies in both reactors, higher BD concentrations could be obtained.